PELATIHAN DRUMBAND BERBASIS KEARIFAN LOKAL TERINTEGRASI NILAI-NILAI ISLAM PADA GURU SEKOLAH DASAR NEGERI MANUNGGAL BHAKTI - Irna Khaleda Nurmeta; Luthfi Hamdani Maula; Muhammad Rizky Syifaurrahmat; Ida Indriyani; Nisrina Sofiliandini Sakinah (As-Sidanah, 2025)
Extracurricular activities can be used as a means to develop students' interests and talents and achieve achievements at school. One of the success factors in extracurricular activities is the role of competent coaches. Teachers can become coaches in extracurricular activities to support extracurricular activities. One way to carry out these extracurricular activities is to provide training to teachers to become coaches in extracurricular activities. The purpose of this training is to realize the cadreship of teachers as coaches in sustainable drumband extracurricular activities. The method used in this community service activity is the CBR method. Activities are carried out on teachers. The training includes basic drumband training, the use of musical instruments in each drumband section, playing intro songs to the ending and combined exercises for blocking and finishing. The results of this training activity show that this activity can provide a foundation for carrying out drumband extracurricular activities in the future. With teachers who have the competence to train extracurricular activities, teachers can collaborate to carry out drumband extracurricular activities to develop students' interests and talents in order to achieve achievements for the school.